Gender-related differences in the outcome of patients with venous thromboembolism and thrombophilia. Issue 151 (March 2017) - Tzoran, Inna; Papadakis, Emmanouil; Brenner, Benjamin; Valle, Reina; López-Jiménez, Luciano; García-Bragado, Fernando; Riera-Mestre, Antoni; Villalobos, Aurora; Quintavalla, Roberto; Monreal, Manuel; ,
ABSTRACT: Background: In patients with venous thromboembolism (VTE) and factor V Leiden (FVL) or prothrombin 20210 G-A mutation (PTM), the influence of gender on outcome has not been consistently studied. Methods: We used the RIETE (Registro Informatizado Enfermedad TromboEmbolica) database to assess the existence of gender differences in the rate of VTE recurrences (deep vein thrombosis [DVT] or pulmonary embolism [PE]) or major bleeding during the course of anticoagulation and after its discontinuation in FVL and PTM carriers. Results: From March 2001 to September 2016, 11, 224 VTE patients underwent thrombophilia testing. Of these, 1, 563 were FVL carriers (863 men and 700 women) and 1, 231 were PTM carriers (659 men and 572 women). During the course of anticoagulant therapy, men with FVL had a 6-fold higher rate of VTE recurrences than major bleeds (31 vs. 5 events). In women with FVL, the rate of VTE recurrences was 2-fold higher (16 vs. 8), as was in men (17 vs. 8) or women (17 vs. 9) with PTM. After discontinuing anticoagulation, men with FVL had a 3-fold higher rate of DVT recurrences than women (hazard ratio [HR]: 3.13; 95% CI: 1.79–5.67), with no differences in PE recurrences. Among patients with PTM, there were no gender differences in the rate of DVT (HR: 1.89; 95% CI: 1.00–3.65) or PE recurrences (HR: 1.82; 95% CI: 0.83–4.12). Conclusions: During the anticoagulation course, men with FVL are at a much higher risk for VTE recurrences than bleeding. After discontinuing anticoagulation, men with FVL are at an increased risk for DVT recurrences.